Perancangan Sistem Filtering Akses Website Dengan Menerapkan Otorisasi LDAP Grup Pada Proxy Server - Prasetya, Noven Indra (INTEGER: Journal of Information Technology, 2016)
Improper use of the internet could negatively impact on users, especially students. This is because a lot of their time is spent just to access websites and online game services providers or friendship website known as social media, even used to access and download images or videos that fall into the category of pornography. Therefore, it needs a system that can be used to restrict access to the internet usage in the campus area, with the aim to overcome the problems that occur with the better. This study was undertaken to design a system that can be used to restrict user access to the website address which is intended to implement the system of filtering access to websites on the Proxy Server, as well as a way to authorize users based on the type of account that is used to access the Internet using a mechanism classification account based group on Lightweight Directory Access Protocol. If his account common types, then the user will not be able to access the game's website, social media, and even pornography. However, if his account special types, such as its example is a lecturer, then the user can access all websites except websites that contain pornography. So that the system is built is expected to reduce the use of the Internet that is not useful, especially campus environment, and the use of internet facilities can be beneficial to both for teaching and learning environment of the campus.